Isolation of H2S-generating Bacterium (Desulfovibrio sp.) and Vibrio parahaemolyticus From Aquatic Farming and In Vitro Evaluation of the Ability of Bacteriophages as Biocontrol - Van, Truong Thi Bich; Loan Anh, Nguyen Thi; Huu Tri , Nguyen; Tuan, Chau Thanh (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract   Highlight Research H2S-generating bacterium (Desulfovibrio) and Vibrio sp. Were idenfied and surveyed its charecteristics. Bacteriophages, ɸTT1H, ɸTT2H, and ɸA2223, could reduce Desulfovibrio vulgaris and Vibrio parahaemolyticus colony sizes and change the bacterial shapes. The bacteriophages could not reduce Desulfovibrio vulgaris and Vibrio parahaemolyticus colony quantity. The bacteriophages affected neither the nucleotide sequence ToxR genes of Vibrio parahaemolyticus nor the 16S rRNA of Desulfovibrio vulgaris.     Abstract Shrimp farming is an important industry in many countries. However, the leftover feed in shrimp ponds can create harmful compounds like H2S and provide a breeding ground for Vibrio bacteria, which causes acute hepatopancreatic necrosis disease. Antibiotics are commonly used to treat this disease, but they can lead to bacterial resistance and environmental pollution. Therefore, using bacteriophages as a treatment option is a more sustainable approach. The present study aimed to isolate H2S-generating bacteria and bacteriophages capable of inhibiting Vibrio sp. and Desulfovibrio sp. from shrimp pond water. Bacteria were identified through biochemical and molecular biology tests. The study utilized plaque and spread methods to observe changes in bacterial number and colony morphology. The study successfully isolated the bacterial strain Desulfovibrio vulgaris (12D) from shrimp ponds. Three potential bacteriophage strains, ɸTT1H, ɸTT2H, and ɸA2223, were identified that have the ability to inhibit Desulfovibrio vulgaris and V. parahaemolyticus bacteria by altering the size, shape, and number of colonies in treatments supplemented with phages. Although they do not alter the nucleotide sequence of these two bacterial strains, they still have a significant effect on controlling the bacterial population. Among the three potential bacteriophage lineages, ɸTT2H was able to inhibit Desulfovibrio vulgaris, reducing the colony quantity by 2.9%. This research allowed researchers to apply bacteriophages to shrimp culture.